Linking supervisor incivility with job embeddedness and cynicism: The mediating role of employee self-efficacy - Uju Violet Alola; Simplice Asongu; Andrew Adewale Alola (African Governance and Development Institute (AGDI), 2019)
Applying the conservation of resources theory and the self-efficacy theory, this study investigates the relationship between supervisor incivility, self-efficacy, cynicism and the job embeddedness of employees in the hotel industry. The role of self-efficacy, as an important variable that mediates the relationship between the predictor and the criterion variable, is significantly evaluated. A non-probability sampling technique was used to collect 245 questionnaires from frontline employees of five- and four-star hotels in Nigeria. The findings reveal that supervisor incivility has a negative effect on self-efficacy and a positive effect on cynicism, and that self-efficacy negatively affects cynicism. There was no significant relationship with job embeddedness in the study. Importantly, the investigation establishes that self-efficacy is a mediating variable between supervisor incivility and cynicism. The study noted the importance of adopting a policy that introduces periodic seminars and professional training for both employees and supervisors, as a means for curbing incivility and cynicism. The study concludes with theoretical and practical implications, leaving room for further investigation.
Keywords: D23; E71; M12; O55; 330; supervisor incivility; cynicism; self-efficacy; job embeddedness; Nigeria